CALCULATIONS OF FLOW FORMATION FOR EXTREME AND EXTREME PHENOMENA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The goal of the article is to study the mechanics of the processes of formation of aspiration flows, to use this process as an additional mechanism for ensuring safety. This goal is solved by the development of a device for determining the aspiration air flows that arise additionally in the combustion process. The results of tests are given for various building structures. It is proposed to use knowledge of the strength of aspiration flows as an additional safety mechanism. Option of an additional mechanism for ensuring safety in case of fire.